Modification of the masses of the lightest neutral mesons in a hadronic medium under an external magnetic field - Aguirre, Ricardo Miguel (2017)
The effective masses of the neutral mesons in a hadronic medium and under an external magnetic field are evaluated as functions of the baryonic density and the field intensity. For this purpose, the meson polarization is evaluated in the one-loop approximation using a quantum hadrodynamics model which includes π, σ, ω, and ρ mesons. The propagators of the baryons include the full effect of the coupling to the magnetic field through their charges and their anomalous magnetic moments. Within the range of magnetic intensities considered here 1017 G, the dependence on B is moderate for the pion and the longitudinal component of the ω meson and negligible for the remaining mesons.